Consumer behaviour towards sponsored-labelled targeted advertisements on Meta platforms in the context of Mauritius - Bindah, Eric; Gunnoo, Leenshya (Journal of Business Economics and Management, 2024)
The purpose of this research is to investigate the effectiveness of ‘sponsored’ labelled targeted ads in Mauritius and whether these ads can impact the brand awareness and purchase intention of Meta group social media users. By adopting the Uses and Gratification Theory (UGT), this research brings forward a conceptual model of six constructs (customisation, informativeness, entertainment, intrusiveness, brand awareness and Purchase intention) to quantitatively understand the effectiveness of targeted ads on Meta Platforms. A sample of 382 students participated in the survey, where 333 valid responses were used for further analysis. In this research, Confirmatory Factor Analysis was utilised to examine the measurement model for brand awareness, customization, informativeness value, entertainment value, intrusiveness value, and purchase intention. The fit indices indicated a reasonable fit between the model and the data. Using Structural Equation Modelling to test the model, the regression weight between customisation, informativeness, entertainment, intrusiveness and brand awareness were statistically significant. The regression weight between brand awareness and purchase intention was also statistically significant. Practically, the findings emphasize the need for marketers and advertisers to invest in strategies that effectively increase brand awareness through targeted advertising.